High HIV Prevalence and Low HIV-Service Engagement Among Young Women Who Sell Sex: A Pooled Analysis Across 9 Sub-Saharan African Countries. (1st October 2020) - Rucinski, Katherine B.; Schwartz, Sheree R.; Mishra, Sharmistha; Phaswana-Mafuya, Nancy; Diouf, Daouda; Mothopeng, Tampose; Kouanda, Seni; Simplice, Anato; Kouame, Abo; Cham, Bai; Tamoufe, Ubald; Matse, Sindy; et al.
Abstract : Background: Epidemiological data are needed to characterize the age-specific HIV burden and engagement in HIV services among young, marginalized women in sub-Saharan Africa. Setting: Women aged ≥18 years who reported selling sex were recruited across 9 countries in Southern, Central, and West Africa through respondent driven sampling (N = 6592). Methods: Individual-level data were pooled and age-specific HIV prevalence and antiretroviral therapy (ART) coverage were estimated for each region using generalized linear mixed models. HIV-service engagement outcomes (prior HIV testing, HIV status awareness, and ART use) were compared among women living with HIV across age strata (18–19, 20–24, and ≥25 years) using generalized estimating equations. Results: By age 18%–19%, 45.4% [95% confidence interval (CI): 37.9 to 53.0], 5.8% (95% CI: 4.3 to 7.8), and 4.0% (95% CI: 2.9 to 5.4) of young women who sell sex were living with HIV in Southern, Central, and West Africa respectively. Prevalence sharply increased during early adulthood in all regions, but ART coverage was suboptimal across age groups. Compared with adult women ≥25, young women aged 18–19 were less likely to have previously tested for HIV [prevalence ratio (PR) 0.76; 95% CI: 0.72 to 0.80], less likely to already be aware of their HIV status (PR 0.48; 95% CI: 0.35 to 0.64), and less likely to be taking ART (PR 0.67; 95% CI: 0.59 to 0.75). Conclusions: HIV prevalence was already high by age 18–19 in this pooled analysis, demonstrating the need for prevention efforts that reach women who sell sex early in their adolescence. ART coverage remained low, with women in the youngest age group the least engaged in HIV-related services. Addressing barriers to HIV service delivery among young women who sell sex is central to a comprehensive HIV response. Abstract : Supplemental Digital Content is Available in the Text.